Pengujian Prototip Suspensi Aktif Tegar (Robust) Model Seperempat Kendaraan - Nyoman Bangsing (Journal of Mathematical and Fundamental Sciences, 2004)
In this paper the result of the performance test of a robust-active suspension system will be presented. The performance of the developed suspension system was evaluated under a sinusoidal road disturbance with amplitude of 3 mm (peak to peak), and within the frequency test range of 1 "“ 9 Hz. The experimental results show that in the frequency test range of 1 "“ 4 Hz, the sprung mass acceleration of the active suspension is smaller than that of the passive suspension. However, the sprung mass acceleration of the active suspension is higher than that of the passive one, in the frequency test range of 5 "“ 9 Hz. Moreover, the unsprung mass acceleration of the active suspension is smaller than its passive counterpart in all of the frequency test range 1 "“ 9 Hz.